The prognosis of liver resection for patients with four or more colorectal liver metastases has not improved in the era of modern chemotherapy. Issue 8 (28th September 2016) - Hokuto, Daisuke; Nomi, Takeo; Yamato, Ichiro; Yasuda, Satoshi; Obara, Shinsaku; Yoshikawa, Takahiro; Kawaguchi, Chihiro; Yamada, Takatsugu; Kanehiro, Hiromichi; Nakajima, Yoshiyuki
Abstract : Background and Objectives: The impact of perioperative chemotherapy on patients with multiple colorectal liver metastases (CRLM) remains unclear. We attempted to examine whether the introduction of modern chemotherapies has improved the prognosis of patients that undergo liver resection for ≥4 CRLM. Methods: Between January 1990 and December 2013, 194 patients underwent liver resection for CRLM at our institution. The outcomes of the patients with ≥4 and 1–3 CRLM were compared before and after 2005, when modern chemotherapies were introduced to Japan. Results: There were 50 and 144 patients with ≥4 (Group 1) and 1–3 (Group 2) CRLM, respectively. The overall survival (OS) rate of Group 1 was significantly worse than that of Group 2 ( P = 0.0007). The OS rate of Group 2 was significantly better after 2005 than before 2004 ( P = 0.039), while no such differences were observed in Group 1. Multivariate analysis identified three prognostic factors in Group 1: a serum carcinoembryonic antigen level of ≥20 ng/ml ( P = 0.018), a serum cancer antigen 19–9 level of ≥100 U/ml ( P = 0.018), and a primary colorectal cancer N factor of ≥N2 ( P = 0.023). Conclusions: The prognosis of patients with ≥4 CRLM that undergo liver resection has not improved despite the development of modern chemotherapies. J. Surg. Oncol. 2016;114:959–965 . © 2016 Wiley Periodicals, Inc.